STUDI PENGARUH UKURAN BUTIR PARTIKEL DAN STRUKTUR KRISTAL TERHADAP SIFAT DIELEKTRIK NANOPARTIKEL COBALT FERRITE (CoFe2O4) - , RAHMAT WIDODO, Dr. Edi Suharyadi, M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cobalt Ferrite (CoFe2O4) has been synthesized with various grain size of particle of 4.3 nm, 7.7 nm, 8.7 nm, 9.0 nm and 9.7 nm using coprecipitation methods then the result was pressed with 50.000N of force to be pellet with diameter of 1 2.26 mm. The measurement uses computerized impedance spectroscopy in the range of frequency 10 kHz to 120 kHz to investigate its dielectric behaviour toward frequence and grain size changes of CoFe2O4. The result shows that real dielectric constant, imaginary dielectric constant, and loss dielectric increase and tend to constant with the increasing of frequency